3D bathymetry reconstruction from airborne topsar polarized data - Marghany, Maged; Hashim, Mazlan; Cracknell, Arthur P. (Springer Berlin / Heidelberg, 2007)
This paper introduces a new methods for three-dimensional(3D) ocean bathymetry reconstruction using Airborne TOPSAR Synthetic Aperture data. The new method is based on integration between Fuzzy B-spline and Volterra algorithm. Volterra algorithm is used to simulate the ocean surface current from TOPSAR data. Then, ocean surface current information used as input for continuity equation to estimate the water depths at different locations in TOPSAR data. This study shows that 3D ocean bathymetry can be reconstructed from TOPSAR data. The maximum water depth of 20 m can be captured from TOPSAR data.